Asymmetric tandem conjugate addition and reaction with carbocations on acylimidazole Michael acceptors - Mudráková, Brigita; Marcia de Figueiredo, Renata; Campagne, Jean-Marc; Šebesta, Radovan (Beilstein Journal of Organic Chemistry, 2023)
We present here a stereoselective tandem reaction based on the asymmetric conjugate addition of dialkylzinc reagents to unsaturated acylimidazoles followed by trapping of the intermediate zinc enolate with carbocations. The use of a chiral NHC ligand provides chiral zinc enolates in high enantiomeric purities. These enolates are reacted with highly electrophilic onium compounds to afford densely substituted acylimidazoles. DFT calculations helped to understand the reactivity of the zinc enolates derived from acylimidazoles and allowed their comparison with metal enolates obtained by other conjugate addition reactions.
Keywords: acylimidazole; asymmetric catalysis; carbocation; conjugate addition; enolate